THE CONTRIBUTION OF CERTAIN PHYSICAL TESTS IN DEVELOPING THE SKILL PERFORMANCE LEVEL IN FOOTBALL FOR JUNIORS - T.Dr. Ahmed Ali Abdullah Ahmed Al-Jubouri; A. T. Ibrahim Ahmed Najm; A.T. SALIM IBRAHIM ALI (Scholars Digest Publishing, 2024)
Using pre- and post-measurements for each group, the researcher employed an experimental design with two groups—one experimental and one control. The North Oil Club Academy's young football players for the 2023 training season made up the research population. In order to represent 50% of the research population, a sample of 36 juniors was purposefully selected, and they were split into two equal groups of 18 juniors each at random. Between the pre- and post-measurements of the experimental group, there were statistically significant changes in favor of the post-measurement regarding the level of contribution of specific physical tests in raising the skill performance level of junior football players. With notable variations in the improvement rate in the contribution of specific physical tests in developing the skill performance level in junior football players in favor of the experimental group, the suggested training program demonstrated a positive impact on improving the components of specific physical fitness (speed, agility, accuracy, and speed-strength).
Keywords: Physical tests, skill performance level, juniors.